Influence of Current Intensity and Heat Input in MIG-Brazed Joints of DP 600 Thin Zinc Coated Steel Plates - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In this study, DP 600 (Dual-Phase) steel plates having 1 mm thickness were joined by copper-based CuAl8 wire in gas metal arc brazing technique. Specimens were prepared as butt joint. Brazing operations were done with ten different arc voltages and weld currents as 40, 45, 50, 55, 60, 65, 70, 75, 80 and 85 A. Tensile strength, bending force, microstructure of brazed materials, and their microhardness distribution throughout joining were determined. In macro and microstructure examinations, stereo optical microscope, scanning electron microscope (SEM) and energy dispersive spectroscopy were used. This study investigated the effects of current intensity on microstructure and microhardness distribution of transition zone between DP 600 steel and MIG-brazed joint. The tensile strength and bending resistance increase with increasing current intensity.
Keywords: MECHANICAL-PROPERTIES